1981
DOI: 10.1128/jcm.13.2.272-278.1981
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human rotaviruses in Melbourne, Australia, from 1973 to 1979, as determined by electrophoresis of genome ribonucleic acid

Abstract: Rotaviruses contain a double-stranded ribonucleic acid genome consisting of 11 segments. Gel electrophoresis separates genome segments and allows identification of strain differences. This electrophoretic typing technique was applied to rotavirus specimens from 116 children and 72 newborn babies. Between 1973 and 1979, 17 different electropherotypes of rotavirus were observed in children with acute gastroenteritis. These electropherotypes showed a sequential pattern of appearance, with a limited number of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
115
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(132 citation statements)
references
References 30 publications
16
115
1
Order By: Relevance
“…Our results have further demonstrated the extensive genomic heterogeneity of rotaviruses and the occurrence of different RNA patterns within an outbreak, as published by others [3,10,12]. However, some remarkable findings of our survey should be noted: no «short» electrophoresis patterns were detected, in contrast to many other reports.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our results have further demonstrated the extensive genomic heterogeneity of rotaviruses and the occurrence of different RNA patterns within an outbreak, as published by others [3,10,12]. However, some remarkable findings of our survey should be noted: no «short» electrophoresis patterns were detected, in contrast to many other reports.…”
Section: Discussionmentioning
confidence: 90%
“…The observation of a predominant electrophoretype in a.given rotavirus season is in agreement with results of other studies-reported from many parts of the world [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotavirus may become endemic in such units and under these circumstances infected babies often remain asymptomatic (Chrystie, Totterdell and Banatvala, 1978). Evidence for this situation was provided by a study of the RNA profiles of rotaviruses affecting neonates in a unit in JJelbourne (Rodger et al, 1981). In this study, certain strains of virus persisted in the unit for a period of up to four years and differed from strains circulating in the community during this time.…”
Section: Enteric Viruses In Hospital-acquired Infectionmentioning
confidence: 88%
“…Oligonucleotide mapping has also been used to study the evolution of influenza A virus strains in nature (Nakajima et al, 1978;Nakajima et al, 1980;Young and Palese, 1979). Electropherotyping of human rotavirus strains has been used to identify strains involved in disease outbreaks within hospital settings and in different parts of the world (Albert et al, 1982;Chiba et al, 1984;Rodger, et al, 1981;Rodriguez et al, 1983;Spencer et al, 1983). This technique has been useful in confirming the difference in rotavirus strains isolated in China from previously recognized rotavirus strains (Hung et al, 1984).…”
Section: Rna Genome Analysismentioning
confidence: 99%